2021
DOI: 10.1038/s41467-021-25745-7
|View full text |Cite
|
Sign up to set email alerts
|

C3 complement inhibition prevents antibody-mediated rejection and prolongs renal allograft survival in sensitized non-human primates

Abstract: Sensitized kidney transplant recipients experience high rates of antibody-mediated rejection due to the presence of donor-specific antibodies and immunologic memory. Here we show that transient peri-transplant treatment with the central complement component C3 inhibitor Cp40 significantly prolongs median allograft survival in a sensitized nonhuman primate model. Despite donor-specific antibody levels remaining high, fifty percent of Cp40-treated primates maintain normal kidney function beyond the last day of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 67 publications
(62 reference statements)
1
34
0
Order By: Relevance
“…As the crucial location of complement activation, C3 and C5 have been considered as the leading therapeutic targets in many inflammatory diseases ( 63 ). Although some complement inhibitors have failed in clinical trials for GA ( 35 37 , 64 ), broad attention of strategic potential of complement inhibition had been aroused by the promising results from phase 3 trials of pegcetacoplan (APL-2, a pegylated C3 inhibitor peptide; Apellis Pharmaceuticals) and phase 2/3 trial of avacincaptad pegol (Zimura, a pegylated RNA aptamer to inhibit C5; IVERIC bio Inc.) ( 38 , 39 ). Now, five complement inhibitors have been investigated in limited number of registered clinical trials regarding to treatment of nAMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the crucial location of complement activation, C3 and C5 have been considered as the leading therapeutic targets in many inflammatory diseases ( 63 ). Although some complement inhibitors have failed in clinical trials for GA ( 35 37 , 64 ), broad attention of strategic potential of complement inhibition had been aroused by the promising results from phase 3 trials of pegcetacoplan (APL-2, a pegylated C3 inhibitor peptide; Apellis Pharmaceuticals) and phase 2/3 trial of avacincaptad pegol (Zimura, a pegylated RNA aptamer to inhibit C5; IVERIC bio Inc.) ( 38 , 39 ). Now, five complement inhibitors have been investigated in limited number of registered clinical trials regarding to treatment of nAMD.…”
Section: Discussionmentioning
confidence: 99%
“…Given the strong association between CNV and complement activation, complement inhibitors are among the few promising options for potential therapy of nAMD. Although initial efforts of complement-targeted therapies have failed to halt GA progression in dry AMD (35)(36)(37), recent results from phase 3 trials of pegcetacoplan (APL-2, Apellis Pharmaceuticals) and phase 2/3 trial of avacincaptad pegol (Zimura, IVERIC bio Inc.) have demonstrated optimized results showing reduction of GA lesion growth (38,39). Until now, no complement inhibitor has been approved by the U.S. Food and Drug Administration (FDA) or European Medicines Agency as treatment for nAMD.…”
Section: Introductionmentioning
confidence: 99%
“…Although these three pathways are engaged by distinct molecular mechanisms, all of them lead to the cleavage of the C3 protein, generating the C3a and C3b fragments ( 118 ). Two recent studies have demonstrated that in a nonhuman primate model, C3 complement inhibition can prevent antibody-mediated injury and improve transplant outcomes ( 119 , 120 ). Ultimately, full complement cascade activation leads to the cleavage of C5, generating the soluble C5a and C5b fragments.…”
Section: Mechanisms Involved In Antibody-mediated MVImentioning
confidence: 99%
“…A clinical study demonstrated that early intervention with eculizumab can reduce C5 activation, restore renal function, and reduce TMA recurrence in subjects with malignant hypertension. 73 Drugs targeting the upstream region of the complement cascade, such as the C3 inhibitor compstatin, 74 have been gradually developed. In theory, these drugs can block the formation of C3 convertase to exert a stronger biological inhibitory effect.…”
Section: Complement Inhibition Is a Potential Treatment Strategy For ...mentioning
confidence: 99%